Novel acoustic coupling bath using magnetite nanoparticles for MR‐guided transcranial focused ultrasound surgery. Issue 12 (29th October 2019) - Allen, Steven P.; Steeves, Tom; Fergusson, Austin; Moore, Dave; Davis, Richey M; Vlaisialjevich, Eli; Meyer, Craig H.
Abstract : Purpose: Acoustic coupling baths, nominally composed of degassed water, play important roles during transcranial focused ultrasound surgery. However, this large water bolus also degrades the quality of intraoperative magnetic resonance (MR) guidance imaging. In this study, we test the feasibility of using dilute, aqueous magnetite nanoparticle suspensions to suppress these image degradations while preserving acoustic compatibility. We examine the effects of these suspensions on metrics of image quality and acoustic compatibility for two types of transcranial focused ultrasound insonation regimes: low‐duty cycle histotripsy procedures and high‐duty cycle thermal ablation procedures. Methods: Magnetic resonance guidance imaging was used to monitor thermal ablations of in vitro gel targets using a coupling bath composed of various concentrations of aqueous, suspended, magnetite nanoparticles in a clinical transcranial transducer under stationary and flowing conditions. Thermal deposition was monitored using MR thermometry simultaneous to insonation. Then, using normal degassed water as a coupling bath, various concentrations of aqueous, suspended, magnetite nanoparticles were placed at the center of this same transducer and insonated using high‐duty cycle pulsing parameters. Passive cavitation detectors recorded cavitation emissions, which were then used to estimate the relative number of cavitation events per insonation (cavitation duty cycle) and the cavitation dose estimates of each nanoparticle concentration. Finally, the nanoparticle mixtures were exposed to low‐duty cycle, histotripsy pulses. Passive cavitation detectors monitored cavitation emissions, which were used to estimate cavitation threshold pressures. Results: The nanoparticles reduced the MR signal of the coupling bath by 90% in T2‐ and T2*‐weighted images and also removed almost all imaging artifacts caused by coupling bath motion. The coupling baths caused <5% changes in peak temperature change achieved during sonication, as observed via MR thermometry. At low duty cycle insonations, the nanoparticles decreased the cavitation threshold pressure by about 15 ± 7% in a manner uncorrelated with nanoparticle concentration. At high duty cycle insonations, the 0.5 cavitation duty cycle acoustic power threshold varied linearly with nanoparticle concentration. Conclusions: Dilute aqueous magnetite nanoparticle suspensions effectively reduced MR imaging artifacts caused by the acoustic coupling bath. They also attenuated acoustic power deposition by <5%. For low duty cycle insonation regimes, the nanoparticles decreased the cavitation threshold by 15 ± 7%. However, for high‐duty cycle regimes, the nanoparticles decreased the threshold for cavitation in proportion to nanoparticle concentration.